Penyuluhan Islam: Membangun Etika dan Akhlak Unggul Bagi Remaja - Jannah, S. Fatyatul; Jalaluddin, Moh.; Baidawi, Baidawi; Makhtumah, Sitti; Rosadi, Imran; Anwari, Moh. (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2024)
Ethics and morals among teenagers are still considered to be low, as evidenced by many of them not adhering to or ignoring the advice of their parents or teachers at school. The goal of this community service is to provide a deep understanding of ethics and morals simultaneously. The service is carried out using the PAR approach with the aid of laptops, LCD projectors, and sound systems. The results show that the activity proceeded very well and was attended by all students present at the service location. The service began with providing specific material on ethics and morals. The students were able to provide good feedback to the presenters and understand the material provided. In conclusion, the community service ran smoothly and had a very positive impact on the students specifically and the school in general.